Application of The Habituation Method in Improving Student Learning Discipline - Abdullah; Umar Manshur (EDUCARE: Jurnal Ilmu Pendidikan, 2023)
This study aims to describe the application of habituation methods in improving student learning discipline in the madrasah environment. The phenomenon of low learning discipline, such as lateness, non-compliance with assignments, and violations of school rules, indicates the need for an appropriate strategic approach in forming positive student learning behavior. The research method used is a qualitative descriptive approach, with data collection through participatory observation, structured interviews, and documentation. This study uses data analysis of the Miles and Huberman model, including data reduction, data presentation, and drawing conclusions, and data validation is carried out through triangulation and continuous observation. The results of the study indicate that the dominant form of application of the habituation method consists of five main elements: rules, punishments, rewards, consistency, and role models. These five elements are consistently applied by teachers and schools to form a disciplined learning routine. The implications of these findings indicate that the habituation method can form more orderly and consistent learning behavior, reduce violations of school rules, and increase student motivation and responsibility in the learning process. This study makes an important contribution to the development of classroom management strategies that are oriented towards character formation through a structured habit approach.